Comparación de celdas fotovoltaicas monocristalina y policristalina en condiciones climáticas de bogotá (2022)
This project aims to compare two photovoltaic panels: one with monocrystalline technology and another with polycrystalline technology, considering the characteristic curves, current - voltage (I-V) and power - voltage (P-V). Initially, simulations of the electrical generation of the panels were carried out taking into account the theoretical model with the internal parameters and the variables radiation, temperature, current, voltage and power. Following, the necessary electronic instrumentation was carried out to measure the irradiance and temperature on the panels, as well as the electrical variables. Finally, a proof of concept was carried out based on an experimental set-up that allowed comparing the behavior of the two technologies. From the experimental tests, it was concluded that the monocrystalline technology panel presented a higher efficiency with respect to the polycrystalline technology panel.